Manufacturing and properties of ferromagnetic aluminum nitride doped with nonmagnetic impurities - Khludkov, Stanislav S.; Prudaev, Ilya A.; Root, L. O.; Tolbanov, Oleg P.; Ivonin, Ivan V. (Russian physics journal)
The review of literature on AlN doping with nonmagnetic impurities (elements of groups I, II, III, and IV of both subgroups and rare earth elements), providing ferromagnetic properties, is presented. The magnetic and electrical properties of AlN are considered in detail. It follows from theoretical and experimental investigations that AlN doped with nonmagnetic impurities has ferromagnetic properties at temperatures above room temperature and is a promising material for spintronics.